If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -25 = 6x + -34 Reorder the terms: -25 + 9x = 6x + -34 Reorder the terms: -25 + 9x = -34 + 6x Solving -25 + 9x = -34 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -25 + 9x + -6x = -34 + 6x + -6x Combine like terms: 9x + -6x = 3x -25 + 3x = -34 + 6x + -6x Combine like terms: 6x + -6x = 0 -25 + 3x = -34 + 0 -25 + 3x = -34 Add '25' to each side of the equation. -25 + 25 + 3x = -34 + 25 Combine like terms: -25 + 25 = 0 0 + 3x = -34 + 25 3x = -34 + 25 Combine like terms: -34 + 25 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| -8x+29=61 | | y=-log(3)*(3x-6) | | v/3-4=1 | | 2.3+1.8a=5.1 | | 0x=-14 | | 2.1b+45.2=3.2-8.4b | | 8-t=10-7 | | z/11=11 | | 8-7=k/11 | | w+11=12 | | 12v+12v=1 | | a/3=6-1 | | -1y-2x=9 | | 100/45=14 | | 5m+24=29 | | 9+14=y | | 6x-280=180 | | 12x+14x+3y= | | -x-41=4(5x-5) | | 4(2x-3)-10=5x+5 | | X+6x-280=180 | | x/50=0.20 | | 2(x+6.2)+2.2=8.7x+7 | | -8.3=5(-1.4-b) | | 2x+y=264 | | 8(s-1)-6.1=2.9s+8 | | (2x-1)/3=1-x | | 14m+4n-5m+7n= | | (2x-1)/3=1_x | | z=4x^2+y^2-6x | | 2(x-3)=3(2x-10) | | -9(5f-4)=-31+3f |